Effect of processing conditions on oil point pressure of moringa oleifera seed - Aviara, N. A. (J Food Sci Technol, 2014)
Seed oil expression is an important economic venture in rural Nigeria. The traditional techniques of carrying out the operation is not only energy sapping and time consuming but also wasteful. In order to reduce the tedium involved in the expression of oil from moringa oleifera seed and develop efficient equipment for carrying out the operation, the oil point pressure of the seed was determined under different processing conditions using a laboratory press. The processing conditions employed were moisture content (4.78, 6.00, 8.00 and 10.00 % wet basis), heating temperature (50, 70, 85 and 100 °C) and heating time (15, 20, 25 and 30 min). Results showed that the oil point pressure increased with increase in seed moisture content, but decreased with increase in heating temperature and heating time within the above ranges. Highest oil point pressure value of 1.1239 MPa was obtained at the processing conditions of 10.00 % moisture content, 50 °C heating temperature and 15 min heating time. The lowest oil point pressure obtained was 0.3164 MPa and it occurred at the moisture content of 4.78 %, heating temperature of 100 °C and heating time of 30 min. Analysis of Variance (ANOVA) showed that all the processing variables and their interactions had significant effect on the oil point pressure of moringa oleifera seed at 1 % level of significance. This was further demonstrated using Response Surface Methodology (RSM). Tukey’s test and Duncan’s Multiple Range Analysis successfully separated the means and a multiple regression equation was used to express the relationship existing between the oil point pressure of moringa oleifera seed and its moisture content, processing temperature, heating time and their interactions. The model yielded coefficients that enabled the oil point pressure of the seed to be predicted with very high coefficient of determination.